1984
DOI: 10.1093/bja/56.12.1417
|View full text |Cite
|
Sign up to set email alerts
|

Computer Assistance in the Control of Depth of Anaesthesia +

Abstract: A control system was used to bring the tension of anaesthetic in the brain to any value specified (in MAC units) by the anaesthetist and then maintain it constant until a new value was specified. The control was applied to a volatile agent but allowance was automatically made for the anaesthetic effect of any nitrous oxide concomitantly administered by the anaesthetist. The inspired concentration required to achieve the desired brain tension was calculated from a model of the patient and set automatically on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…7). A similar ability to demonstrate a second gas effect influencing nitrous oxide uptake is present in version "S" of Mapleson's original model (Chilcoat, 1983).…”
Section: Discussionmentioning
confidence: 56%
“…7). A similar ability to demonstrate a second gas effect influencing nitrous oxide uptake is present in version "S" of Mapleson's original model (Chilcoat, 1983).…”
Section: Discussionmentioning
confidence: 56%
“…However, for an inhalation-only anaesthetic, the target should, basically, be a constant partial pressure at the site (or sites) of action which, in terms of the model, must mean a constant brain partial pressure. To achieve this quickly requires end-expired, and even arterial 'overpressure' [27] -not just the inspired overpressure of Figs 3 and 4. With sufficient trial and error, the model could be used to devise a suitable sequence of flows and partial pressures but the assumption of constancy of cardiac output and its distribution would no longer be valid.…”
Section: Discussionmentioning
confidence: 99%
“…These authors further report that, at the moment of induction, there was less hypotension with the slowest injection rate. This could be explained by following Chilcoat, Lunn and Mapleson [29] in assuming that the "blood-pressure control centre" is better perfused than the "induction-of-anaesthesia control centre": the simulation showed that, in a compartment with four times the specific perfusion of the sample brain compartment (actually the kidney), Cs at the moment of induction with the slowest injection rate was 70 % of that with the normal rate.…”
Section: Effects Of Speed Of Injectionmentioning
confidence: 99%